STRATEGI KOMUNIKASI PROGRAM SIARAN ACARA â€œKETIBAN SAMPURâ€ DALAM MEMPERTAHANKAN LOYALITAS PENDENGAR (STUDI KASUS: RRI SURABAYA PRO 4 96,8 SURABAYA) - Sidi, Theresia Ine Sintya; Sudaryanto, Edy; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2019)
Radio is one of the mass media that is closely related to the needs of the community that can provide various kinds of information, entertainment, and education. RRI Surabaya is also one radio station that has 4 programs in it and each program has its own characteristics. Programa (Pro) 4 for example covers cultural broadcasts and one of them is